Challenges and Innovations in Postoperative Care for Acute Type A Aortic Dissection: The Role of Structured Surveillance and Virtual Wards - Robert Pruna-Guillen; Laerke Ghosh; Tara M. Mastracci; Vikas Kapil; Ana Lopez-Marco; Aung Oo (Reviews in Cardiovascular Medicine)
Acute Type A aortic dissection (ATAAD) represents a life-threatening medical emergency that requires emergent surgical repair. Despite improvement in surgical techniques and perioperative management, ATAAD remains associated with high early mortality and postoperative complications. A structured and individualized postoperative surveillance program is essential, not only for improving survival rates but also for identifying risk factors necessitating reintervention and enhancing the quality of life. Comprehensive postoperative care should address both medical monitoring and psychological support to meet the holistic needs of ATAAD survivors. In real-world settings adherence to guideline-directed imaging surveillance (GDIS) is poor, leading to underestimation of reintervention rates. A comprehensive aortic service should include GDIS, clinical assessments, cardiovascular risk management, and psychological support. Since August 2022, a virtual ward has been implemented in our department to facilitate remote monitoring, ensuring tight blood pressure control and early detection of complications.